China import competition and El Salvador manufacturing firm performance - Kun Li; Mauricio Mesquita Moreira (Inter-American Development Bank (IDB), 2019)
In this paper, we analyze the impact of Chinese competition on manufacturing firms in El Salvador between 2005 and 2013 using manufacturing survey data and customs transaction data. We find that Chinese import competition in El Salvador has a negative effect on firms employment, total factor productivity (TFP), and revenue. A 1-percentage-point increase in the measure of Chinese import competition in El Salvador reduces the employment of production workers by 2.27%. The negative impact is mainly reflected in employment at firms with less than 50 employees and those with low capital intensity. A 1-percentage-point-increase in the measure of Chinese import competition in El Salvador reduces low-productivity firms TFP by 1.851%, and total revenue of the low-revenue firms by 3.241%. Chinese competition in El Salvador export markets increases the production-worker employment at large firms, reduces TFP at medium-productivity firms, reduces the total revenue of low productivity firms, and increase the total revenue of high-productivity firms. In general, firm offshoring has no effect.
Keywords: F14; L25; L60; 330; Chinese competition; employment; productivity; manufacturing firms in El Salvador